The Influence of Environment and Leader Member Exchange (LMX) on State Civil Apparatus (ASN) Work Productivity at The Head Office of XYZ Government Agency - Ananda Fortunisa; Devinda Sari Dewantini (Publikasi Indonesia, 2024)
This study aims to analyze the influence of the work environment and Leader Member Exchange (LMX) variables such as respect, trust, interactive roles, Influence, Loyalty, Contribution, Professional Respect and rewards on the work productivity of State Civil Apparatus (ASN) at the Head Office of the XYZ Government Institution. This study uses a quantitative approach with a survey method, and data analysis is carried out using SmartPLS. The results of the study indicate that the work environment has an effect on work productivity, in the LMX variable most of the variables studied have a significant influence, namely Respect, Influence, Loyalty and Rewards on ASN work productivity and other variables such as Trust, Interactive Roles, Contributions and Professional Respect do not have a significant effect on ASN work productivity at the XYZ Institution Head Office. On the other hand, other variables related to LMX, such as trust, interactive roles, contributions, and professional respect, did not show a significant influence on ASN's work productivity.